Effect of Risk Assessment Practices on Expenditure Management of Government Organization in Rivers State - Onowu Joseph Uche; Azali Sophia Iguehi (International Journal on Economics, Finance and Sustainable Development, 2022)
The study investigated internal audit practices and expenditure management of government organizations in Rivers state. The specific objectives of the study among others were to; determine the effect of risk assessment on aggregate fiscal discipline of government organizations in Rivers State, determine the effect of risk assessment on allocation efficiency of government organizations in Rivers State and determine the effect of risk assessment on operational efficiency of government organizations in Rivers State. This study adopted survey research design. The population comprised of 5 selected government owned organizations in Rivers state. The study adopted simple sampling techniques, the research utilized primary and secondary data. The research questions were analyzed using descriptive statistics, while the formulated hypotheses were tested using the multiple regression analysis with the aid of SPSS and E=View. From the findings of the analysis, amongst others, showed that that risk assessment has significant effect on allocation efficiency on government organizations in Rivers State. risk assessment has no significant effect on operational efficiency on government organizations in Rivers State. The following recommendations are made among others; Auditors independence should be non-negotiable and sacrosanct in government organizations if operational efficiency is to be achieved. On no account should auditors’ independence be jettisoned in public sector organization that seeks to sustain operational efficiency. Government organizations’ staff should update their knowledge with respect to risk assessment and allocation efficiency through the opportunities provided by information and communication technology solutions so as to be able to benefit from the strategic values of effective and efficient public expenditure management.